2017
DOI: 10.1080/14767058.2017.1418316
|View full text |Cite
|
Sign up to set email alerts
|

The effect of prophylactic oral tranexamic acid plus buccal misoprostol on blood loss after vaginal delivery: a randomized controlled trial

Abstract: In settings like rural area or home delivery in which oxytocin is not available, alternative oral TA plus buccal misoprostol may be considered as an effective line in prevention of PPH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…examining the true potential of oral TXA. Nevertheless, a study testing 1000 mg oral TXA at the end of the first stage of labor followed by misoprostol showed that this regimen was associated with lower blood loss when compared to prophylactic IV oxytocin [11]. Another limitation of our study is that the rates of intervention were very different from our assumptions for sample size calculation (above).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…examining the true potential of oral TXA. Nevertheless, a study testing 1000 mg oral TXA at the end of the first stage of labor followed by misoprostol showed that this regimen was associated with lower blood loss when compared to prophylactic IV oxytocin [11]. Another limitation of our study is that the rates of intervention were very different from our assumptions for sample size calculation (above).…”
Section: Discussionmentioning
confidence: 83%
“…Whereas IV TXA is recommended for use in the treatment of PPH, oral TXA may not confer the same effect as IV administration, which allows for much greater bioavailability [11]. Therefore, it is possible that the misoprostol treatment (in addition to other interventions), may have effectively controlled blood loss before oral TXA could take effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of bias was assessed independently by LH and AW for 14 trials [10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Six assessments [24][25][26][27][28][29] were produced during a review by Gallos et al [30].…”
Section: Risk Of Bias Of Included Trialsmentioning
confidence: 99%
“…[4][5][6] rectal and intrauterine. [7][8][9][10] Beside that, it can be used for termination of pregnancy in cases of missed or incomplete miscarriage. [11][12][13] Also, in cases with retained placenta it may have a role in management of associated bleeding which mostly result from atony.…”
Section: Introductionmentioning
confidence: 99%